Edukasi Literasi Keuangan Digital Bagi Masyarakat RW 14 Kelurahan Uwung Jaya Kecamatan Cibodas Kota Tangerang - Siti Asriah Immawati; Lena Erdawati; Rosyid Rosyid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In line with the development of higher information technology, resulting in people easily accessing all information, especially in shopping online, investing online, making online loans and gambling online, this certainly requires strong household financial management. Conducting digital financial literacy education in the community is one solution to reduce the impact of errors due to improper management and to reduce the gap between understanding financial literacy and financial inclusion in the community. With the delivery of digital financial literacy education, it is hoped that the community will be able to manage household finances wisely.